Breathlessness and opioid prescribing in COPD in general practice: a cross-sectional, observational study. Issue 2 (6th July 2020) - Currow, David C.; Johnson, Miriam J.; Pollack, Allan; Ferreira, Diana H.; Kochovska, Slavica; Ekström, Magnus; Harrison, Christopher
Chronic breathlessness is a disabling syndrome, prevalent in people with advanced chronic obstructive pulmonary disease (COPD). Regular, low-dose, oral sustained-release morphine is approved in Australia to reduce symptomatic chronic breathlessness. We aimed to determine the current prescribing patterns of opioids for chronic breathlessness in COPD in Australian general practice and to define any associated patient and practitioner characteristics. Five years (2011 to 2016) of the Bettering the Evaluation and Care of Health database, an Australian national, continual, cross-sectional study of clinical care in general practice were used. The database included 100 consecutive clinical encounters from almost 1000 general practitioners annually (n=488 100 encounters). Descriptive analyses with subsequent regression models were generated. Breathlessness as a patient-defined reason for encounter was identified in 621 of 4522 encounters where COPD was managed. Opioids were prescribed in 309 of 4522 encounters where COPD was managed (6.8%; (95% CI) 6.1–7.6), of which only 17 were prescribed for breathlessness, and the rest for other conditions almost entirely related to pain. Patient age (45–64 years versus age 80+ years, OR 1.68; 1.19–2.36), Commonwealth Concession Card holders (OR 1.70; 1.23–2.34) and socioeconomic disadvantage (OR 1.30; 1.01–1.68) were associated with increased likelihood of opioid prescription at COPD encounters. The rate of opioid prescriptions rose over the 5 years of study. In primary care encounters for COPD, opioids were prescribed in 6.8% of cases, but almost never for breathlessness. These data create a baseline against which to compare changes in prescribing as the treatment of chronic breathlessness evolves. In COPD, one in 13 people is prescribed opioids by family physicians in Australia, but rarely for chronic breathlessness https://bit.ly/2XO1Ol8